Gastric Cancer Diagnosis: From Imaging Techniques to Biochemical Biomarkers - Tavakoli, Fatemeh; Khatami, Sara S.; Momeni, Fatemeh; Azadbakht, Javid; Ghasemi, Faezeh (Current Molecular Medicine, 2021)
Gastric cancer (GC) has been found to be the second leading cause of cancer-associated deaths in the world, and is usually detected in the advanced stages. It has been shown that surgery is the major therapeutic approach in the treatment of subjects with GC. Hence, early and fast diagnosis of this malignancy is very important for good subject outcomes. Non-invasive diagnostic platforms, including evolutionary endoscopy and positron emission tomography (PET), are employed for the diagnosis of subjects with GC. Along with imaging techniques, the utilization of biomarkers has emerged as a new diagnosis option for early and fast detection of GC. Multiple lines of evidence have revealed a variety of biomarkers, including microRNAs, exosomes, circulating tumor cells, circular RNAs, cell free DNAs, and various proteins, which could be used as diagnostic biomarkers in patients with GC. Taken together, these findings suggest that the joint application of imaging techniques and different biomarkers could be introduced as a new detection approach in the treatment and screening response to therapy in the subjects with GC. Herein, we have summarized various imaging techniques and biomarkers as powerful tools in the detection of GC.
Keywords: diagnostic biomarkers